(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The article presents the results of the study the accumulation of heavy metals (Mn, Co, Ni) in the plants of the lower reaches of the river. Ile. As a result of our research was found that the dominant plants in selected Glycyrrhiza glabra and Xantium strumarium actively accumulate heavy metals, nickel and manganese that exceed the MCL.